Penggunaan Multimedia Dalam Pembelajaran PAI Untuk Meningkatkan Hasil Belajar Siswa Di SMKN 1 Sumatera Barat - Mutmainnah, Devi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students' learning outcomes through the use of multimedia in Islamic Religious Education (PAI) lessons with the topic "Understanding the Rules of Prayer." The research employs a classroom action research (CAR) method conducted in two cycles. The results show a significant improvement in students' learning outcomes, with the average score increasing from 79 in Cycle I to 89 in Cycle II and classical completeness rising from 59% to 94%. The use of multimedia, including PowerPoint presentations, animations, videos, songs, quizzes, and interactive games, enhanced students' motivation, understanding, and engagement in learning. Furthermore, reflections from Cycle II indicate that multimedia usage should be continuously developed by teachers to improve the quality of learning. This study concludes that multimedia is an effective tool for enhancing students' learning outcomes in Islamic Religious Education.